The Relationship Between The Level of Nutritional Knowledge, Consumption Patterns and The Level of Per Capita Income with The Incidence of Chronic Energy Deficiency (KEK) in Pregnant Women - Istiqomah, Deya Nadya; Farhat, Yasir; Rahmani (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2025)
Riskesdas South Kalimantan in 2018 reported that in South Kalimantan Province the prevalence of chronic energy deficiency in pregnant women was increase. In the Landasan Ulin Timur Health Center area, Banjarbaru City is ranked first in KEK for pregnant. This study aims to determine the relationship between the level of nutritional knowledge, consumption patterns and the level of per capita income with the incidence of chronic energy deficiency (KEK) in pregnant women in the working area of the Landasan Ulin Timur Community Health Center, Banjarbaru City. This research method is analytical observational with a case control design. The population in this study was all 361 pregnant women in the working area of the Landasan Ulin Timur Community Health Center, Banjarbaru City. The number of samples in this study was 44 people using purposive sampling technique. With a case count of 1:1. Cases were 22 pregnant women with CED and controls were 22 pregnant women who were not CED. Collecting data on the level of nutritional knowledge, consumption patterns, and level of per capita income with KEK incidence using interviews and questionnaires. Data analysis used the Spearman Rank test. The results of this study indicate that the level of nutritional knowledge of pregnant women with KEK is poor (72.8%). The consumption patterns of pregnant women with SEZ are low (81.8%), and the per capita income level of pregnant women with SEZ is low (90.9%). There is a relationship between the level of nutritional knowledge, consumption patterns, and the level of per capita income and the incidence of CED in pregnant women. It is hoped that pregnant women will consume a balanced diet according to their needs. And community health centers should provide outreach or counseling to increase pregnant women's knowledge regarding nutrition regarding KEK.